2010
DOI: 10.1002/prca.200900086
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic protein marker patterns in squamous cervical cancer

Abstract: SCC is characterized by specific tissue marker protein patterns that allow objective detection of the disease. They can become a basis for objective automated cytology-based screening and improve current diagnostics of SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 39 publications
(51 reference statements)
4
54
0
1
Order By: Relevance
“…Of all the cervical malignancies, 70-80% are squamous cell cervical carcinoma (SCC) originating from squamous cell epithelia (SCEs) (25).…”
Section: Roles Of Anxa6 In Cervical Cancer Progression and Malignancymentioning
confidence: 99%
See 3 more Smart Citations
“…Of all the cervical malignancies, 70-80% are squamous cell cervical carcinoma (SCC) originating from squamous cell epithelia (SCEs) (25).…”
Section: Roles Of Anxa6 In Cervical Cancer Progression and Malignancymentioning
confidence: 99%
“…A number of studies have demonstrated that AnxA6 is associated with the progression and malignancy of CC, and it is a potential protein marker for SCC development (25,40). Proteomic results of Lomnytska et al (25) demonstrated that AnxA6 was overexpressed in SCC, and the N-terminus of AnxA6 was upregulated 2-fold in SCC compared with cervical mucosa (CM).…”
Section: Roles Of Anxa6 In Cervical Cancer Progression and Malignancymentioning
confidence: 99%
See 2 more Smart Citations
“…Cathepsin D is an aspartic acid protease which has been studied as a potential biomarker with increased expression in colorectal cancer, while its high levels have been linked to metastatic events (45). Furthermore, it has been reported to be highly secreted from lung cancer cell lines (46) and up-regulated in vaginal cancer compared to cervical cancer (47), playing also a role as a biomarker in breast cancer (48). Pro-cathepsin D has been found to be secreted from cancer cells and bound either by stromal cells inducing the proliferation of fibroblasts and further promoting carcinogenesis or by endothelial cells, and promoting angiogenesis.…”
Section: Discussionmentioning
confidence: 99%